Diagnostic Efficacy of Hysteroscopy and Its Use as a Therapeutic Aid in Perimenopausal and Postmenopausal Women - See and Treat - Akkenapally Prasanna Latha; Vasundhara Kamineni; Jaligama Vishal Prabhu (Wolters Kluwer Medknow Publications, 2024)
Aim The aim of this study was to study the therapeutic role of hysteroscopy in peri- and postmenopausal women in certain pathological conditions, where it can be done as a single-time procedure to diagnose and operate wherever needed and possible. Objective The objective of this study was to measure the diagnostic accuracy of hysteroscopy and its therapeutic efficacy in peri- and postmenopausal women. Introduction Hysteroscopy is one of the accurate diagnostic procedures in diagnosing the cause of peri- and postmenopausal bleeding (PMB). It can also be used to treat few benign conditions of peri- and PMB. Here, in our study, we tried to evaluate the accuracy of hysteroscopy in diagnosing the cause of peri- and PMB and its use in treating certain conditions of PMB. Materials and Methods The study design is a prospective observational study; women with peri- and PMB were recruited for 1 year and followed for consecutive 3 years. Based on hysteroscopic findings and after confirming the histopathological examination report, women were treated. Women who did not need any further surgical procedures after operative hysteroscopy were followed for recurrence in benign conditions. Women with premalignant and malignant lesions underwent simple or radical hysterectomy soon after diagnosis. Results A total of 71 women were enrolled in the study who fulfilled the inclusion criteria. There were 20 perimenopausal and 51 postmenopausal women, the mean age was 56.02 years. Most of the women presented with PMB (56.3%) or heavy menstrual bleeding (18.3%). Hysteroscopy has 83.34%, 100%, 100%, 98.46%, and 0.98% of sensitivity, specificity, positive predictive value, negative predictive value, and accuracy, respectively, in diagnosing carcinomas. Out of 71 women, 58 were diagnosed with benign conditions, 6 had carcinoma, 7 had premalignant conditions, these 13 women with malignant or premalignant conditions underwent further surgical management as per protocol. 58 women who did not need any further surgical procedure, and hysteroscopy was sufficient to treat their condition were followed up for 3 consecutive years, 4 had recurrence of endometrial polyps, 6 had recurrence of bleeding and needed hysterectomy, thus in our study by means of hysteroscopy we could prevent hysterectomy in 67.7% of women with benign endometrial conditions. Conclusion In conditions with benign endometrial polyps and fibroid polyps, hysteroscopy is very much useful for both diagnosis and treatment, which can be performed as a one-time procedure. Although this serves the purpose only in a small segment of women with peri- and PMB, it is needed in the prevention of unnecessary hysterectomies.